2016
DOI: 10.1097/brs.0000000000001349
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Outcome in Posterior Spinal Fusion for Adolescent Idiopathic Scoliosis

Abstract: 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 27 publications
(26 reference statements)
1
40
1
Order By: Relevance
“…The framework introduced here promises a surgical decision-making tool that can be personalized for physicians based on their preferred techniques. The rod length and curvature (using the EP clusters) can be determined prior to surgery to reduce the operation room time and number of staff which in turns reduces the surgical cost as well as blood loss and risk of infection 44 , 50 , 51 . Moreover, as the patients’ expectation plays an important role in their satisfaction, self-image, and quality of life after surgery 52 54 , by exploring the possible outcomes, a more comprehensive expectation of the surgical outcomes can be achieved by the patient, patient’s family, and their surgeon as they go through the process of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The framework introduced here promises a surgical decision-making tool that can be personalized for physicians based on their preferred techniques. The rod length and curvature (using the EP clusters) can be determined prior to surgery to reduce the operation room time and number of staff which in turns reduces the surgical cost as well as blood loss and risk of infection 44 , 50 , 51 . Moreover, as the patients’ expectation plays an important role in their satisfaction, self-image, and quality of life after surgery 52 54 , by exploring the possible outcomes, a more comprehensive expectation of the surgical outcomes can be achieved by the patient, patient’s family, and their surgeon as they go through the process of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…[ 12 ] In another prospective study of patients with adolescent idiopathic scoliosis undergoing posterior spinal fusion, Chan and Kwan found that surgery performed by 2 surgeons results in decreased operative time, blood loss, postoperative morphine usage, and hospital length of stay compared with single surgeon teams. [ 14 ] These results were mirrored in subgroups of patients with Lenke 1 and 2 curves. [ 15 , 16 ] Similarly, Abousamra et al found decreased operative time and blood loss in spine surgery performed by 2 attending surgeons as compared with a single surgeon in patients with CP.…”
Section: Discussionmentioning
confidence: 90%
“…Fifty-five retrospective studies, nine prospective studies, and three randomized controlled trials were included. There were 17 multi-center studies [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: Resultsmentioning
confidence: 99%